MARKET DEVELOPMENT MODEL OF WATER REFILL BUSINESS VIDINI JEMBER - Sudaryanto Sudaryanto; Anifatul Hanim; Nanik Istiyani (UPT Penerbitan Universitas Jember, 2022)
This study aims to build a conceptual mapping of Vidini's refill water service marketing strategy in winning industry competition. The paradigm used is prepositive nominalist qualitative, namely by developing concepts based on environmental conditions. It was formulated that the marketing strategy was not only convenient but also using digital media. Keywords: marketing strategy, conceptual mapping, refill water, qualitative